(untitled) (Bangladesh Journal of Zoology, 2022)
The study was undertaken to isolate and identify the bacteria from the gut of honey bees and to investigate their antibiotic sensitivity. A total 35 honey bees were collected from Sher-e-Bangla Agricultural University and Curzon Hall area of Dhaka city. This study was conducted to identify the gram-positive and gram-negative bacteria based on the morphological features using microscope. In this study, four species of honey bees were identified, of which, Apis dorsata was the most dominant (31.43%) species and followed by 17.14% for Apis cerana and 2.86% for Apis mellifera and Apis florea, respectively. In total, five gram-positive bacteria genera including Lactobacillus sp. (37.5%), Streptococcus sp. (9.38%), Staphylococcus sp. (21.88%), Enterococcus sp. (6.25%), and Clostridium sp. (9.38%); and two gram-negative bacteria i.e., Pseudomonas sp. (3.13%), and Enterobacter sp. (12.5%) were detected. Gram-positive bacteria were the most dominant at the honey bee gut in two sites, while bacteria did not detect in A. dorsata gut which was collected from Sher-e-Bangla Agricultural University. However, five types of bacteria were isolated from the gut of A. dorsata collected from Curzon Hall area. In total, the highest varieties (6 out of 7) and number of isolates (15) were found from A. florea. Whereas, the highest number of bacteria was isolated from A. florea (12) for Curzon Hall area, and A. cerana (6) for Sher-e-Bangla Agricultural University. In antibiotic susceptibility test, the isolated Streptococcus sp., Staphylococcus sp. and Enterococcus sp. were sensitive to the majority of the antibiotics. However, the isolated Lactobacilllus sp., Clostridium sp., Enterobacter sp. and Pseudomonas sp. were resistant to the majority of antibiotics. The results show that the presence or absence of bacterium in honey bees gut was an indicator for their overall health. Bangladesh J. Zool. 50 (1): 83-93, 2022